ANALISIS PENGARUH PEMBIASAAN SALAT DUHA BERSAMA TERHADAP PEMBENTUKAN KARAKTER SISWA SEKOLAH DASAR - Nenden; Asep Sahrul Gunawan (STKIP Subang, 2026)
Character education is a fundamental aspect in the formation of students' personalities from an early age, especially at the elementary school level. Religious character in Islam means moral behavior that is in accordance with what is taught in Islamic education. This study aims to analyze in depth the influence of the habit of praying duha together on character formation in elementary school students. This research is based on the importance of strengthening character education in the midst of the phenomenon of declining moral values and student discipline. The method used in this study is a literature study, with data collection techniques from 12 SINTA-indexed journal articles from previous research that are relevant to the analysis of the influence of the habit of duha prayer together on the formation of the character of elementary school students. The results of this study show that the duha prayer together has a significant influence on the formation of students' character, especially in the aspects of religion, discipline, responsibility, and honesty. Activities that are carried out regularly and in a structured manner are able to internalize character values through direct experience (learning by doing), making it more effective than a theoretical approach alone. Therefore, the habit of praying duha together can be a strategy for implementing character education in elementary schools.